THE PLOT OF THE CHARACTERS IN ALL THE BRIGHT PLACES/KARAKTER DALAM ALUR CERITA ALL THE BRIGHT PLACES - Patricia Dharma Widyantara; I Gusti Agung Istri Aryani; Ni Luh Nyoman Seri Malini (Balai Bahasa Provinsi Bali, 2020)
Abstract Nowadays, plot within characters with mental health issues still a sensitive issue to be discussed by most people. Some parents often avert their children from the exposure of the topics in the purpose to protect them suffering the same illness. It is important to discuss on this topic since intend to show the reality of individuals’ feeling as mentioned in the plot of this study. The novel of All the Bright Places managed to succeed in delivering the message through interesting plot development where two main characters get together and share their perspectives to carry out the story. Hence, this study aims to investigate how Niven as a story writer structured her story with the plot. The results of this study showed a progressive kind of plot where plot elements are chronologically arranged within the mental health issues. These were found from the language in the plot including their point of views and symbols used as the elements of ction shown in the exposition, complication, crisis, climax, falling action, and resolution. It seemed that there were connection between characters supported with the language use and events covered inside the plot. These re ected to the whole part of patterns inside the story that give personal touchs to their readers from the events. Keywords: ction, literature, mental illness, novel, plot Abstrak Dewasa ini, pembahasan alur cerita dengan karakter-karakter yang memiliki masalah kejiwaan masih dianggap sensitif bagi kebanyakan orang. Beberapa orang tua masih sering menghindarkan anaknya dari paparan topik tersebut demi alasan keamanan supaya tidak terkena penyakit yang sama. Pengangkatan topik ini penting sebab berusaha mengungkapkan perasaan seseorang secara nyata dalam alur cerita seperti kajian ini. Pada novel “All the Bright Places” berhasil menyajikan pembahasan yang memberikan alur cerita menarik melalui sudut pandang kedua tokoh utama yang secara berdampingan dibagikan dalam memandu perkembangan alur cerita. Studi ini bertujuan untuk mengetahui bagaimana cara Niven sebagai penulisnya mengemas alur ceritanya. Hasil penelitian membuktikan bahwa Niven mengadaptasi tipe alur cerita progresif karena urutan alur yang tersusun secara kronologis dengan permasalahan kejiwaan di dalamnya. Temuan berupa penggunaan bahasa termasuk sudut pandang dan simbol-simbol sebagai unsur-unsur dalam alur cerita yaitu ekposisi, komplikasi, krisis, klimak cerita, penurunan klimak dari alur cerita, dan resolusi. Keterkaitan antara karakter-karakter, bahasa dan kejadian-kejadian yang ada turut mendukung alur cerita itu. Hal ini mere eksikan bahwa pola-pola kejadian yang ada mengalir di dalam cerita sehingga dapat memberikan sentuhan mendalam kepada pembacanya. Kata kunci: fiksi, kesusastraan, masalah kejiwaan, novel, alur cerita